The Role of Peer Support in Promoting EFL Achievement: Academic Self-Concept as the Mediator - Wu, Yajun; Kang, Xia (Universitas Muhammadiyah Malang, 2023)
For secondary school students, peer support is an essential component of social support, which might significantly influence their academic achievement. However, the mediating mechanism between peer support and academic achievement needs to be further explored, especially in teaching English as a foreign language (EFL). The present study explored the relationship between peer support, foreign language (FL) self-concept, and EFL achievement based on the data of 499 Chinese secondary EFL learners. Structural equation modelling (SEM) and mediation analysis results demonstrated that peer support positively affected EFL achievement. FL self-concept fully mediated the relationship between peer support and EFL achievement after controlling for gender and age. The direction and strength of the mediating effect of FL self-concept between peer support and EFL achievement clarify the complex relationship between peer support and EFL achievement and helps EFL teachers and educators take intervention measures. Implications, limitations and directions for future research are discussed.